Analyzing the Role of E-Government in Enhancing Public Services and Governance - Fitri Melawati (urn:multiple://2988-7828multiple.v3i48)
This study examines the transformative impact of e-government initiatives on public service delivery and governance mechanisms across various contexts. Through a qualitative descriptive approach utilizing library research methodology, this research synthesizes existing knowledge to provide a comprehensive understanding of how digital governance tools reshape the relationship between citizens and government. The analysis reveals that successful e-government implementation depends on technological infrastructure, policy frameworks, institutional capacity, and citizen engagement. Key benefits include improved service efficiency, transparency, accountability, and citizen participation, while challenges encompass digital divides, privacy concerns, cybersecurity threats, and implementation barriers. The study identifies critical success factors for e-government initiatives and proposes a framework for evaluating their effectiveness in enhancing public services and governance. This research contributes to the scholarly discourse on digital transformation in the public sector and offers practical insights for policymakers and public administrators seeking to leverage technology for effective governance.